The handedness of historiated spiral columns. Issue 5 (3rd September 2017) - Couzin, Robert
ABSTRACT: Trajan's Column in Rome (AD 113) was the model for a modest number of other spiral columns decorated with figural, narrative imagery from antiquity to the present day. Most of these wind upwards to the right, often with a congruent spiral staircase within. A brief introductory consideration of antique screw direction in mechanical devices and fluted columns suggests that the former may have been affected by the handedness of designers and the latter by a preference for symmetry. However, for the historiated columns that are the main focus of this article, the determining factor was likely script direction. The manner in which this operated is considered, as well as competing mechanisms that might explain exceptions. A related phenomenon is the reversal of the spiral in a non-trivial number of reproductions of the antique columns, from Roman coinage to Renaissance and baroque drawings and engravings. Finally, the consistent inattention in academic literature to the spiral direction of historiated columns and the repeated publication of erroneous earlier reproductions warrants further consideration.